Bidimensional Extensions of Cobalancing and Lucas-Cobalancing Numbers - Chimpanzo J.; Otero-Espinar M.V.; Borges A.; Vasco P.; Catarino P. (Annales Mathematicae Silesianae, 2024)
A new bidimensional version of cobalancing numbers and Lucas-balancing numbers are introduced. Some properties and identities satisfied by these new bidimensional sequences are studied.